Advanced glycation end-products (AGEs) accumulation in skin: relations with chronic kidney disease-mineral and bone disorder - França,Renata de Almeida (2017)
Abstract Introduction: Chronic kidney disease (CKD) is associated with high morbidity and mortality rates, main causes related with cardiovascular disease (CVD) and bone mineral disorder (CKD-BMD). Uremic toxins, as advanced glycation end products (AGEs), are non-traditional cardiovascular risk factor and play a role on development of CKD-BMD in CKD. The measurement of skin autofluorescence (sAF) is a noninvasive method to assess the level of AGEs in tissue, validated in CKD patients. Objective: The aim of this study is analyze AGEs measured by sAF levels (AGEs-sAF) and its relations with CVD and BMD parameters in HD patients. Methods: Twenty prevalent HD patients (HD group) and healthy subjects (Control group, n = 24), performed biochemical tests and measurements of anthropometric parameters and AGEs-sAF. In addition, HD group performed measurement of intact parathormone (iPTH), transthoracic echocardiogram and radiographies of pelvis and hands for vascular calcification score. Results: AGEs-sAF levels are elevated both in HD and control subjects ranged according to the age, although higher at HD than control group. Single high-flux HD session does not affect AGEs-sAF levels. AGEs-sAF levels were not related to ventricular mass, interventricular septum or vascular calcification in HD group. AGEs-sAF levels were negatively associated with serum iPTH levels. Conclusion: Our study detected a negative correlation of AGEs-sAF with serum iPTH, suggesting a role of AGEs on the pathophysiology of bone disease in HD prevalent patients. The nature of this relation and the clinical application of this non-invasive methodology for evaluation AGEs deposition must be confirmed and clarified in future studies.